GRAND: An Integrated Genome, Transcriptome Resources, and Gene Network Database for Gossypium - Zhang, Zhibin; Chai, Mao; Yang, Zhaoen; Yang, Zuoren; Fan, Liqiang (Frontiers in Plant Science, 2022)
With the increasing amount of cotton omics data, breeding scientists are confronted with the question of how to use massive cotton data to mine effective breeding information. Here, we construct a Gossypium Resource And Network Database (GRAND), which integrates eighteen cotton genome sequences, genome annotations, two cotton genome variations information, and also four transcriptomes for Gossypium species. GRAND allows to explore and mine this data with the help of a toolbox that comprises a flexible search system, BLAST and BLAT suite, orthologous gene ID, networks of co-expressed genes, primer design, Gbrowse and Jbrowse, and drawing instruments. GRAND provides important information regarding Gossypium resources and hopefully can accelerate the progress of cultivating cotton varieties.